Effect of ZnCl2-activated biochar on catalytic pyrolysis of mixed waste plastics for producing aromatic-enriched oil. (November 2018) - Sun, Kai; Huang, Qunxing; Chi, Yong; Yan, Jianhua
Graphical abstract: Highlights: The yield of bicyclic aromatics could reach 90.7% by ZnCl2 activated biochar. One-step ZnCl2 activation increased the specific surface area more efficiently. Two-step ZnCl2 activation was more effective in increasing the loading amount. The use of microemulsion in activation could reduce coke formation by 41.8%. Lewis acid sites formed by Zn species promoted aromatization processes. Abstract: ZnCl2 -activated biochar produced by one-step (impregnated by a 40% ZnCl2 solution, defined as Zn/C-I) and two-step (impregnated by a 40% ZnCl2 solution and microemulsion, defined as Zn/C-II and Zn/C-III, respectively) methods was used to catalyze the pyrolysis of mixed waste plastics (polyethylene, polyethylene, and polystyrene) to comparatively study their catalytic effect on aromatic-enriched oil production. The catalytic mechanism was discussed. The results show that ZnCl2 -activated biochar showed high catalytic selectivity to aromatics during the pyrolysis of plastics at 500 °C, and the content of aromatics was increased to 47.5, 46.8, and 42.4% when respectively catalyzed by Zn/C-I, Zn/C-II, and Zn/C-III. Two-ring aromatics were significantly enriched, which accounted for 90.7, 73.1, and 87.7% of the aromatics in Zn/C-I, Zn/C-II, and Zn/C-III catalytic pyrolysis oils. 1, 3-Diphenylpropane was the major component of the oils, and its proportion was 19.4, 11.5, and 15.9% in Zn/C-I, Zn/C-II, and Zn/C-III catalytic pyrolysis oils, respectively. The introduced Zn species could increase the surface acidity by forming Lewis acid sites (Zn-L), which increased aromatic yields by promoting the Diels–Alder reaction, hydrogen transfer, and dehydrogenation processes. Zn-L also promoted the condensation reaction of aromatics. Compared with Zn/C-I, Zn/C-III treated by ZnCl2 microemulsion could reduce 41.8% of coke on the catalysts owing to its larger pore size, while maintaining a relatively high oil quality.